Dangerous Legacy of Food Contact Materials on the EU Market: Recall of Products Containing PFAS - Carme Ribes Ortega; Alexandra Molitorisová; Kai Purnhagen (European Journal of Risk Regulation)
Toxic substances and endocrine disruptors are present in consumer goods on the European Union (EU) market, such as in food contact materials like cookware. This article investigates whether a legal recall obligation of such products exists in EU law, and in the absence of such an obligation, how the EU legislature has ensured that such products are disposed of in a manner that does not compromise human health and the environment when they become waste. For this purpose, this Article analyses recall obligations for food contact materials containing persistent organic pollutants, as well as their waste regulations. It focuses on a class of substances with non-stick properties, some of them formerly used in cookware, such as pentadecafluorooctanoic acid (PFOA) and perfluorooctane sulfonic acid (PFOS). We show that there is no single legal recall obligation; rather, many legal obligations are scattered among different provisions of EU law. When read together, they form a complex web of obligations, which may lead to recall measures for most of these products. However, doubts over the feasibility and effectiveness of such recalls remain.